Rapid Test Advances in Design, Format and Diagnostic Applications - Anfossi, Laura (IntechOpen, 2018)
Rapid tests, also known as point-of-care tests, have been in use for decades in the clinical and medical area and have become increasingly popular as an efficient screening method for conducting on-site analysis thanks to their simplicity, speed, specificity and sensitivity. Nowadays, rapid tests are widely applied for clinical, drug, food, forensic and environmental analysis and fields of application are rapidly increasing together with advances in the technology. The growing interest in rapid tests and their expanding application in diverse fields, together with requirements of improved sensitivity, reliability, multiple detection capacity and robustness, are prompting innovation in the design of novel platforms, and in the exploitation of innovative detection strategies. The book covers advances in materials, technology and test design.